Second life as a platform for virtual design and manufacturing - Wong, Raymond Tuck Wai. (2009)
Second life is no different from the conventional CAD/CAM software such as AutoCAD, 3dsmax or MAYA because the fundamental element and principle of 3D modeling form the backbone of the alternative platform for virtual design and manufacturing. The only difference is Second life emulating is fully supportive of the user to the users. Through the assistance voice enabled function, users can easily simulate a virtual environment within a short period time due the low learning curve for its 3D modelling input controls and operators. As a result, users can engage in distance learning, within the virtual world. This virtual phenomenon is prominent through the vibrant economy of Second life where millions of dollars is exchanged daily for USD. Therefore, there is a hidden potential of the Second life which anyone can “plug in” and leverage on the virtual platform for virtual design and manufacturing in terms of fashion, advertising, education or engineering design related product through ecommerce within the virtual environment. The shift in paradigm will eventually be more and hardware technologies with ultra fast bandwidth peak in the future. The changes in the way of virtual design and manufacturing for product life cycle will be imminent day comes. Therefore, it is sensible to dive in and explore and exploit the benefits that a virtual environment can offer. Second interactive virtual world mirrored after the real world-generated content creation through granting the virtual IP rights of Second life in-built construction tools and sharing of resources or do collaboration with anyone be more noticeable when the evolution of super computer.